Aucubin slows the development of osteoporosis by inhibiting osteoclast differentiation via the nuclear factor erythroid 2-related factor 2-mediated antioxidation pathway. (1st January 2021) - Zhang, Yongfeng; Liu, Xin; Li, Yangyang; Song, Minkai; Li, Yutong; Yang, Anhui; Zhang, Yaqin; Wang, Di; Hu, Min
Abstract: Context: Osteoporosis (OP) is a metabolic disease. We have previously demonstrated that aucubin (AU) has anti-OP effects that are due to its promotion of the formation of osteoblasts. Objectives: To investigate the mechanisms of anti-OP effects of AU. Materials and methods: C57BL/6 mice were randomly divided into control group, 30 mg/kg Dex-induced OP group (OP model group, 15 μg/kg oestradiol-treated positive control group, 5 or 45 mg/kg AU-treated group), and 45 mg/kg AU-alone-treated group. The administration lasted for 7 weeks. Subsequently, 1, 2.5 and 5 µM AU were incubated with 50 ng/mL RANKL-induced RAW264.7 cells for 7 days to observe osteoclast differentiation. The effect of AU was evaluated by analysing tissue lesions, biochemical factor and protein expression. Results: The LD50 of AU was greater than 45 mg/kg. AU increased the number of trabeculae and reduced the loss of chondrocytes in OP mice. Compared to OP mice, AU-treated mice exhibited decreased serum concentrations of TRAP5b (19.6% to 28.4%), IL-1 (12.2% to 12.6%), IL-6 (12.1%) and ROS (5.9% to 10.7%) and increased serum concentrations of SOD (14.6% to 19.4%) and CAT (17.2% to 27.4%). AU treatment of RANKL-exposed RAW264.7 cells decreased the numbers of multi-nuclear TRAP-positive cells, reversed the over-expression of TRAP5, NFATc1 and CTSK. Furthermore, AU increased the expression of nuclear factor erythroid 2-related factor 2 (Nrf2) and its downstream proteins in RANKL-exposed RAW264.7 cells. Conclusions: AU slows the development of OP via Nrf2-mediated antioxidant pathways, indicating the potential use of AU in OP therapy and other types of OP research.